Invasive and antiplatelet treatment of patients with non‐ST‐segment elevation myocardial infarction: Understanding and addressing the global risk‐treatment paradox. Issue 10 (17th July 2019) - Ahrens, Ingo; Averkov, Oleg; Zúñiga, Eduardo C.; Fong, Alan Y. Y.; Alhabib, Khalid F.; Halvorsen, Sigrun; Abdul Kader, Muhamad A. B. S. K.; Sanz‐Ruiz, Ricardo; Welsh, Robert; Yan, Hongbin; Aylward, Philip
Abstract: Clinical guidelines for the treatment of patients with non‐ST‐segment elevation myocardial infarction (NSTEMI) recommend an invasive strategy with cardiac catheterization, revascularization when clinically appropriate, and initiation of dual antiplatelet therapy regardless of whether the patient receives revascularization. However, although patients with NSTEMI have a higher long‐term mortality risk than patients with ST‐segment elevation myocardial infarction (STEMI), they are often treated less aggressively; with those who have the highest ischemic risk often receiving the least aggressive treatment (the "treatment‐risk paradox"). Here, using evidence gathered from across the world, we examine some reasons behind the suboptimal treatment of patients with NSTEMI, and recommend approaches to address this issue in order to improve the standard of healthcare for this group of patients. The challenges for the treatment of patients with NSTEMI can be categorized into four "P" factors that contribute to poor clinical outcomes: p atient characteristics being heterogeneous; p hysicians underestimating the high ischemic risk compared with bleeding risk; p rocedure availability; and p olicy within the healthcare system. To address these challenges, potential approaches include: developing guidelines and protocols that incorporate rigorous definitions of NSTEMI; risk assessment and integrated quality assessment measures; providing education to physicians on the management of long‐term cardiovascular risk in patients with NSTEMI; and making stents and antiplatelet therapies more accessible to patients.